Characterization of Fluorescence of ANS–Tear Lipocalin Complex: Evidence for Multiple-Binding Modes - Gasymov, Oktay K. (2007)
ANS is widely used as a probe for locating binding sites of proteins and studying structural changes under various external conditions. However, the nature of ANS-binding sites in proteins and the accompanying changes in fluorescence properties are controversial. We examined the steady-state and time-resolved fluorescence of the ANS–protein complexes for tear lipocalin (TL) and its mutants in order to discern the origin of lifetime components via analysis that included the multiexponential decay and the model-free maximum entropy methods. Fluorescence lifetimes of ANS–TL complexes can be grouped into two species, 14.01–17.42 ns and 2.72–4.37 ns. The log-normal analyses of fluorescence spectral shapes reveal the heterogeneous nature of both long- and short-lifetime species. The constructed time-resolved emission, amplitude (TRES) and area normalized (TRANES), and decay-associated spectra are consistent with a model that includes heterogeneous modes of ANS binding with two separate lifetime components. The two lifetime components are not derived from solvent relaxation, but rather may represent different binding modes.